Epistemics for Learning Disabilities: Contributions from Magnetoencephalography, a Functional Neuroimaging Tool - Santiuste Bermejo, Víctor Alfredo; Universidad Complutense de Madrid (Pontificia Universidad Javeriana, 2007)
The syndrome known as Learning Disabilities (LD) was described by S. Kirk in 1963. From that point on, institutions from the US, Canada and Spain have engaged in refining the concept and classification of LDs. The Com- plutense University in Spain, has proposed a descriptive and all-embracing definition, and has studied the different manifestations of LD, pursuing the description of biological markers and neurological features of LD’s main expressions: dyslexia, dyscalculia, dysorthographia, Attention Deficit and Hyperactivity Disorder –ADHD, and so forth. Findings in LD using functio- nal neuroimaging techniques, namely Magnetoencephalography (MEG), are described. MEG is a non-invasive technique, which records magnetic fields naturally generated by the brain and their spatial distribution. It allows simultaneous functional and structural information. MEG is therefore used in the study of primary and superior cognitive functions, in surveillance of patterns of normal cognitive function and those specific to the different LD clinical manifestations.